2005
DOI: 10.2174/1567201053586010
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Evaluation of Guar Gum-Based Matrix Tablets of Rofecoxib for Colonic Drug Delivery

Abstract: The present study was carried out to develop and evaluate guar gum-based matrix tablets of rofecoxib for their intended use in the chemoprevention of colorectal cancer. Matrix tablets containing 40% (RXL-40), 50% (RXL-50), 60% (RXL-60) or 70% (RXL-70) of guar gum were prepared by wet granulation technique, and were subjected to in vitro drug release studies. Guar gum matrix tablets released only 5 to 12% of rofecoxib in the physiological environment of stomach and small intestine. The matrix tablets RXL-40 dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…This slow release also makes slow absorption of the drug and making it available for local action in human colon. [128] Polysaccharide based hydrogels are also prepared to achieve antitumoral drug relesase.…”
Section: Use Of Gum In Development Of Drug Deliverymentioning
confidence: 99%
“…This slow release also makes slow absorption of the drug and making it available for local action in human colon. [128] Polysaccharide based hydrogels are also prepared to achieve antitumoral drug relesase.…”
Section: Use Of Gum In Development Of Drug Deliverymentioning
confidence: 99%
“…Guar gum-based matrix tablets of rofecoxib for their intended use in the chemoprevention of colorectal cancer were developed and evaluated [116]. Matrix tablets containing 40% (RXL-40), 50% (RXL-50), 60% (RXL-60) or 70% (RXL-70) of guar gum were prepared by wet granulation technique.…”
Section: Delayed Onset For Targeting Colon Drug Deliverymentioning
confidence: 99%
“…In vivo studies showed delayed T max , prolonged absorption time and decreased C max indicating that rofecoxib was not released significantly in stomach and small intestine, but was delivered to colon resulting in a slow absorption of the drug and making it available for local action in human colon22.…”
Section: Gumsmentioning
confidence: 99%